2014
DOI: 10.3386/w19880
|View full text |Cite
|
Sign up to set email alerts
|

Media Bias in the Marketplace: Theory

Abstract: We review the theoretical literature on market determinants of media bias. We present a theoretical framework that organizes many key themes in the literature, and discuss substantive lessons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
98
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 46 publications
2
98
0
1
Order By: Relevance
“…Profit The media firm maximizes the advertising revenue, which is assumed to proportionate to the traffic to the firm's news site (Gentzkow, Shapiro and Stone, 2015). The traffic is equivalent to the measure of readers.…”
Section: The Baseline Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Profit The media firm maximizes the advertising revenue, which is assumed to proportionate to the traffic to the firm's news site (Gentzkow, Shapiro and Stone, 2015). The traffic is equivalent to the measure of readers.…”
Section: The Baseline Modelmentioning
confidence: 99%
“…Our work relates to the literature on demand-driven media bias (Gentzkow, Shapiro and Stone, 2015), which means that consumers enjoy reading news that confirm their biased beliefs. Mullainathan and Shleifer (2005) and Gabszewicz, Laussel and Sonnac (2001) use a Hotelling kind of model to explain a possible ideological bias of news.…”
Section: Introductionmentioning
confidence: 99%
“…Allcott and Gentzkow (2017) provide a recent overview of much of the directly related economics literature. They consider the economics of fake news very directly and summarise a model of Gentzkow, Shapiro and Stone (Gentzkow et al, 2016) in which, in contrast to Mullainathan and Shleifer (2005), fake news can be characterised as being uncorrelated with the truth. 'Fake news arises in equilibrium because it is cheaper to 4 Barrera Rodriguez et al (2017) conducted a randomised online experiment with potential French voters during the 2017 presidential election campaign, exposing subjects to quotes from Marine Le Pen, a right-wing candidate, and/or real facts and found that those intending to vote for her were unswayed by correct information.…”
Section: Introductionmentioning
confidence: 99%
“…The literature has moved from assessing the evidence of bias (Groseclose and Milyo, 2005), to estimating the electoral impact of media conglomerates' bias (DellaVigna and Kaplan, 2007;Gentzkow et al, 2011), to discussing the sources of bias in either reputational incentives and other supply sources (Gentzkow and Shapiro, 2006) or in cognitive limitations of readers and viewers and other demand sources (Duggan and Martinelli, 2011;Mullainathan and Shleifer, 2005) or in both supply and demand factors (Bernhardt et al, 2008), to discussing the importance of media for the control of incumbent politicians (Besley and Prat, 2006). The literature is summarized from different perspectives by Prat and Stromberg (2013) and Gentzkow and Shapiro (2015).…”
Section: Introductionmentioning
confidence: 99%